Faktor-faktor yang Mempengaruhi Akuntabilitas Keuangan Pemerintah Daerah Kota Jayapura - Auliyah, Iriana (STIEM BONGAYA, 2023)
This study aims to analyze the effect of the competence of government officials, internal control systems, regional financial information systems on financial accountability in Jayapura City. This research was conducted at the Jayapura City Regional Office, with a planned research time from April 2022 to June 2022. This study used primary data collected directly from respondents, namely a closed questionnaire on a Likert scale with five (5) alternative answers. Based on the results of the study showed that the competence of government officials, internal control systems, regional financial information systems partially or simultaneously, affect the financial accountability of Jayapura City.